PROGRAM LATIHAN FISIOTERAPI BAGI LANSIA UNTUK MENINGKATKAN MOBILITAS DAN KESEIMBANGAN DI PANTI JOMPO YAYASAN EMBUN KEHIDUPAN BANGSA - Nurshal, Rezki Amalia; Mastikana, Indah; Santoso, Fauzan Agus (Awal Bros Journal of Community Development, 2025)
As people age, they experience a decline in physical function, affecting mobility, balance, and independence. This increases the risk of falls and injury, potentially lowering their quality of life. This community service activity aimed to improve the mobility and balance of elderly residents through a physiotherapy program conducted at the Embun Kehidupan Bangsa Nursing Home. The program included health education on the importance of physical activity and physiotherapy exercises tailored to the participants' physical conditions. Additionally, functional assessments were conducted before and after the program to evaluate its effectiveness. The results showed significant improvements in the mobility and balance of the elderly, as well as a reduction in the risk of falls. This program not only improved the physical quality of life of the elderly but also helped build their independence in daily activities. This activity is expected to serve as a model for other nursing homes, highlighting the importance of collaboration between healthcare professionals and the community to enhance the well-being of the elderly.